Political Advertising by Big Business after Rubicon - Paul Vorster (Communicare)
IN South Africa political advertising as mode of political communication is now firmly established and even the Government used paid space to promote its post- Rubicon policy emphasis. While South Af- political parties are strongly refraining from using political advertising (with the qualified exception of the Labour Party of South Africa and the Progressive Federal Party), Big Business emerged as the major political advertiser. This can be explained by the interdependence between politics and economics. However, without being truly accountable to the public, this is a somewhat controversial trend. Therefore, for the future of democracy, political parties as the primary political actors cannot refrain from using all available communication techniques. The effective use of communication techniques in no way diminishes the need for realistic appraisals of the circumstances, sound policies, organisational efficiency and interpersonal contact P with the voters. Deeds still speak louder than words.